PENAMBAHAN TEPUNG LABU KUNING DALAM MENINGKATKAN MUTU KERUPUK SAGU - Ariyanda Putra; Noviar Harun; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research is aimed to find out the effect of yellow pumpkin flour addition toward the content of the nutrition in Sago Chips. From consumers’ point of view, the writer knew that there is the characteristic of censor attribute to the four treatments of sago chips product. This experimental research used Comprehensive Random Program with four treatments and four times tests such as KL1 (100% of sago extract and 0% yellowpumpkin flour), KL2(90% of sago extract and 10% yellowpumpkin flour), KL3(80% of sago extract and 20% yellowpumpkin flour) and KL4(70% of sago extract and 30% yellowpumpkin flour). The data was analyzed statistically by using ANOVA. If F arithmetic were bigger than or as same as F table so the analyze will be continue by using Duncan’s New Multiple Range Test in 5% level. The result of water level was 2.10-4.33%, the dust level was 20.19%-23.89% and the breed capacity was 38.92%-67.80% with unknown quality standard. Consumers’ fondness level toward Sago Chips based on preference mapping were KL1 (100% of sago extract and 0% yellow pumpkin flour) and KL2 (90% of sago extract and 10% yellowpumpkin flour) with had attributes qualitylike sago taste, sago aroma, yellow color and crispy. In the other side, the level of disfavor was KL4 (70% of sago extract and 30% yellowpumpkin flour), the chips from Air Tiris Market, which had attributes quality like garlic taste, garlic, and pumpkin aroma. Keywords: Sago chips, sago extract, yellow pumpkin flour, preference      mapping